The Role of Student College in Moderating Religious Science in the Digital Era - Muhammad Bachrul Alam; Arsan Shanie; Dian Pratiwi; Mey Liana Sinta; Najwa Hanifah; Nofyan Fajry (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: In the digital era, the rapid spread of religious content through online platforms presents both opportunities and challenges for maintaining religious harmony. The need for moderate, inclusive, and contextual religious understanding has become increasingly urgent, especially among younger generations. Objective: This study aims to explore the role of university students in moderating religious knowledge in the digital era. Method: This research uses a qualitative approach with a literature review method. Data were collected from various written sources such as books, scientific journals, articles, and relevant online sources. Data were analyzed using the content analysis method, which included data reduction, data presentation, interpretation, and conclusion drawing. Result: The results showed that students play a strategic role in moderating religious knowledge through social media engagement, dissemination of positive and educational religious content, formation of online interfaith communities, and collaboration with religious leaders and academics to promote religious moderation. Conclusion: University students have significant potential as agents of religious moderation in the digital era, using their digital literacy and social influence to counteract radical narratives and foster inclusive dialogue. Contribution: This research contributes to a deeper understanding of the proactive role of the younger generation, particularly university students, in maintaining religious harmony and promoting moderate religious discourse in the digital landscape.